Penerapan Arsitektur Islam pada Desain Masjid Pondok Pesantren Al Baaits di Takalar - Qadri, Ahmad Al; Rahayu, Irma; Nursyam, Nursyam (TIMPALAJA : Architecture Student Journals, 2024)
Abstract: The pesantren (Islamic boarding school) is a traditional Islamic educational institution in Indonesia with distinct characteristics in its education system and culture, where the mosque's architecture plays a significant role in creating identity and reflecting religious values. This study aims to analyse the façade design of the mosque at Pondok Pesantren Al Baaits, focusing on the influence of Islamic values in the selection of ornaments and decorations, as well as their connection to the concept of safety in both the worldly and afterlife aspects of Islamic architecture. We employed a qualitative approach using a case study method. We gathered data from direct observations of the mosque's façade design, interviews with the pesantren management, and a review of pertinent Islamic architecture literature. The findings show that the front of the mosque at Pondok Pesantren Al Baaits has some Islamic-themed decorations that show how the relationship between people, nature, and God should be balanced between the physical and non-physical worlds. These ornaments strengthen cultural and spiritual identity and create an atmosphere conducive to learning and devotion in both worldly and spiritual contexts.